Pengaruh Permainan Sticky Board Terhadap Kemampuan Literasi Awal Anak Kelompok A - Rapi, Us. Djuko; Waode Eti Hardiyanti; Nur Anisa Abdul Wahab (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
This study aims to determine the influence of the Sticky Board game on the early literacy skills of Group A children at said Kindergarten in the research site. It applied a quantitative pre-experimental design with a one-group pretest-posttest design. The findings revealed a difference in the average scores between the pretest and posttest, based on a sample of 26 children. The pretest data showed an average value of 15.1 and a standard deviation of 3.04, while the posttest data showed an average value of 32.5 and a standard deviation of 2.26. The findings demonstrated a significant influence before and after the implementation. Based on the output of the Statistical Test, the T count value was 17.7, and the T table value was 2.048. Thus, the value was 17.7> 2.048, and the hypothesis is accepted. Therefore, the research hypothesis stated that there is an influence of the Sticky Board Game on the Early Literacy Skills of Group A Children at TK Mekar Wangi Kindergarten in Botubarani Village, Kabila Bone District, Bone Bolango Regency.